Runs and flights to safety: Are stablecoins the new money market funds? - Kenechukwu Anadu; Pablo D. Azar; Marco Cipriani; Thomas M. Eisenbach; Catherine Huang; Mattia Landoni; Gabriele La Spada; Marco Macchiavelli; Antoine Malfroy-Camine; J. Christina Wang (Federal Reserve Bank of Boston, 2023)
Stablecoins and money market funds both seek to provide investors with safe, money-like assets but are vulnerable to runs in times of stress. In this paper, we investigate similarities and differences between the two, comparing investor behavior during the stablecoin runs of 2022 and 2023 to investor behavior during the money market fund runs of 2008 and 2020. We document that, similarly to money market fund investors, stablecoin investors engage in flight to safety, with net flows from riskier to safer stablecoins during run periods. However, whereas in money market funds, run risk has historically materialized only in prime funds, with stablecoins, runs occurred in different stablecoin types across the 2022 and 2023 episodes. We also show that, similar to intrafamily flows in money market funds, stablecoin flows tend to be within blockchains. Finally, for stablecoins, we estimate a discrete "break-the-buck" threshold of 0.99, below which redemptions accelerate.
Keywords: G10; G20; G23; 330; stablecoins; money market mutual funds; financial stability; crypto assets; runs; liquidity transformation